2009
DOI: 10.1103/physrevb.79.085116
|View full text |Cite
|
Sign up to set email alerts
|

Theory of interacting electrons on the honeycomb lattice

Abstract: The low-energy theory of electrons interacting via repulsive short-range interactions on graphene's honeycomb lattice at half filling is presented. The exact symmetry of the Lagrangian with local quartic terms for the Dirac field dictated by the lattice is D_2 x U_c(1) x (time reversal), where D_2 is the dihedral group, and U_c(1) is a subgroup of the SU_c(2) "chiral" group of the non-interacting Lagrangian, that represents translations in Dirac language. The Lagrangian describing spinless particles respecting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
386
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(404 citation statements)
references
References 66 publications
15
386
1
2
Order By: Relevance
“…An "extended" Hubbard model involving an additional interaction term describing nearest neighbor repulsions of strength V has been studied analytically by employing renormalization-group (RG) techniques in the limit of a large number N f of fermion flavors [84,85] (we remind the reader that N f = 4 for electrons in graphene). It has been found [84,85] that sufficiently large values of V /t stabilize charge-density-wave phases over semimetallic or Mott insulating phases.…”
Section: Hubbard Correlations and Split Bandsmentioning
confidence: 99%
See 1 more Smart Citation
“…An "extended" Hubbard model involving an additional interaction term describing nearest neighbor repulsions of strength V has been studied analytically by employing renormalization-group (RG) techniques in the limit of a large number N f of fermion flavors [84,85] (we remind the reader that N f = 4 for electrons in graphene). It has been found [84,85] that sufficiently large values of V /t stabilize charge-density-wave phases over semimetallic or Mott insulating phases.…”
Section: Hubbard Correlations and Split Bandsmentioning
confidence: 99%
“…It has been found [84,85] that sufficiently large values of V /t stabilize charge-density-wave phases over semimetallic or Mott insulating phases. Numerical RG calculations [86] have qualitatively confirmed these results but also discovered that second-neighbor repulsions favor topological states with spontaneously broken time-reversal symmetry (i.e.…”
Section: Hubbard Correlations and Split Bandsmentioning
confidence: 99%
“…[4,5,6,7,8,9,10,11,12,13,14,15,17,16]). There, the predominant ordering tendencies are in the particle-hole channel, and usually superconductivity is not among the leading candidates.…”
Section: Undoped and Weakly Doped Graphenementioning
confidence: 99%
“…A large number of exotic states of matter has been proposed theoretically, see e.g. [4,5,6,7,8,9,10,11,12,13,14,15,16,17], but most have not been experimentally observed as of yet. One exception is multi-layer graphene systems where there are now experimental reports of an energy gap opening at low temperatures, which has been ascribed to interactions effects [18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…20 Extensive studies on interacting graphene have shown a variety of competing phases. [22][23][24] Below we discuss the effects of producing the longer range interactions required for topological order using the Friedel oscillations and Ruderman-Kittel-Kasuya-Yosida (RKKY) interactions occurring in a metallic (Fermi-gas) environment. Our analysis considers the possibility of forming both topological phases as well as other competing phases.…”
Section: Introductionmentioning
confidence: 99%